Impact of exercise-based pulmonary rehabilitation on respiratory function and quality of life in pediatric patients with chronic lung diseases: A multidisciplinary approach in Damietta Governorate - Soliman, Amir; El-Sayed, Mohamed Salah; Hasan, Judy; Shawky, Eman; Hussein Ahmed Arafat, Walid Elsayed; Elmahdy, Menan A.; Eid, Heba A.; Hassan, Shaza S.; Mohamed, Eman K.; Ibrahem Mansour, Ahmed Saadeldeen; et al. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Chronic lung diseases (CLDs) in children, such as asthma, cystic fibrosis, and bronchopulmonary dysplasia, significantly impact respiratory function and overall quality of life. Exercise-based pulmonary rehabilitation (PR) has emerged as a multidisciplinary approach to improving lung function, exercise capacity, and reducing hospitalization rates. This study assessed the effectiveness of a structured PR program in pediatric patients with CLDs in Damietta Governorate, Egypt. A randomized controlled trial was conducted with 400 pediatric patients with CLDs (aged 6–16 years) divided equally into intervention and control groups. The intervention group underwent a 12-week exercise-based PR program incorporating respiratory training, airway clearance techniques, and physical therapy, while children in the control group received standard medical care consisting of routine follow-ups, medication management, and lifestyle counseling without structured rehabilitation exercises. Post-intervention results demonstrated significant improvements in forced expiratory volume (FEV1), forced vital capacity (FVC), peak expiratory flow, six-minute walk test (6MWT), and quality of life scores (p < 0.001). Additionally, hospitalization frequency and medication dependency were significantly reduced (p < 0.001). The findings reveal that exercise-based PR significantly improves pulmonary function, exercise tolerance, and overall quality of life in children with chronic lung diseases. Additionally, PR effectively reduces hospitalization rates and medication dependency, offering a sustainable approach to disease management.